2010
DOI: 10.1287/isre.1100.0296
|View full text |Cite
|
Sign up to set email alerts
|

Information Technology, Network Structure, and Competitive Action

Abstract: R esearchers in competitive dynamics have demonstrated that firms that carry out intense, complex, and heterogeneous competitive actions exhibit better performance. However, there is a need to understand factors that enable firms to undertake competitive actions. In this study, we focus on two antecedents of competitive behavior of firms: (1) access to network resources and (2) use of information technology (IT). We argue that while network structure provides firms with the opportunity to tap into external res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
63
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(65 citation statements)
references
References 82 publications
2
63
0
Order By: Relevance
“…This empirical study revealed that the structural holes in Zhangjiang pharmaceutical innovation network exert significantly positive effects on the organizational innovation capability. This is consistent with the study results of the scholars Burt (, ), Koka & Prescott () and Chi (). Noteworthy, the correlativity between structural holes in Zhangjiang pharmaceutical innovation network and organizational innovation capability is merely 0.28 ( p < .01) which is not significant enough to be considered as a strong correlativity.…”
Section: Discussionsupporting
confidence: 93%
“…This empirical study revealed that the structural holes in Zhangjiang pharmaceutical innovation network exert significantly positive effects on the organizational innovation capability. This is consistent with the study results of the scholars Burt (, ), Koka & Prescott () and Chi (). Noteworthy, the correlativity between structural holes in Zhangjiang pharmaceutical innovation network and organizational innovation capability is merely 0.28 ( p < .01) which is not significant enough to be considered as a strong correlativity.…”
Section: Discussionsupporting
confidence: 93%
“…This enables the IT function to seize opportunities that arise with "speed and surprise" as well as quickly adapt to external developments in areas such as technology and regulation [7,22]. An agile IT function is capable of being proactive and driving the changes that the firm's competitors will need to respond to.…”
Section: It Agilitymentioning
confidence: 99%
“…Gielens et al, 2008) and management information systems (e.g. Chi, Ravichandran, & Andrevski, 2010).…”
Section: Integrative Competitor Analysismentioning
confidence: 99%